Locke on Freedom, Moral Agency, and the Space of Reasons - Viljanen, Valtteri (Locke Studies)

(untitled) (Western Libraries at The University of Western Ontario, 2024)
This paper argues that what interests Locke most is not whether we are free to suspend desire but the nature of the liberty that suspension grants us, and that Lockean liberty is essentially about deliberation that takes place in what has nowadays come to be called the space of reasons. This allows me to offer a novel and balanced account that carefully designates both causal and rational elements of Locke’s theory of moral agency: after having reached a judgment concerning the best course of action, we are to take measures, if need be, so that this cognitive achievement raises the corresponding conative element, namely an uneasiness that determines our will. Locke’s ambitious theory aims to incorporate two strong philosophical intuitions widely held incompatible: that our will is free and that impulses affect our choices. The present interpretation thus throws new light on the development of Western moral thought.